A fart in the corridors of power: A socio-theological analysis of Evan Mawarire and Raymond Mpandasekwa"s activism - Muzambi, Prosper (HTS teologiese studies, 2023)
#ThisFlag movement was started by Pastor Evan Mawarire in April 2016 bemoaning the collapse of the Zimbabwean economy at the hands of the Zimbabwe African National Union-Patriotic Front (ZANU-PF) government under President Robert Mugabe. Although it started off as accidental, it, however, galvanised disparate groups and enabled them to transform anger against the state from online media to the streets. #ThisFlag movement officially started on the 20th of April 2016, when Pastor Mawarire wearing the Zimbabwean flag posted a video to his Facebook page decrying the state of the economy and what he felt was government’s neglect of its duties to serve the citizens of Zimbabwe. Although one government minister described Mawarire’s actions as a ‘pastor’s fart in the corridors of power’, the reaction by the state security agents points to the contrary. Street protests have been banned. This article interrogates the transformation of #ThisFlag movement from an online struggle to street protests that have turned violent. It also looks at other movements that are complementing #ThisFlag and how the state is responding to these protests both on the social media and on the ground. Evan Mawarire may be considered as an unusual voice from the ever mushrooming new church establishments. As such, it becomes a point of interest to find out what voice there is, which represents what is commonly viewed as mainline churches. Such a voice is identified as coming from Bishop Raymond Mpandasekwa of the Roman Catholic Diocese of Chinhoyi who in one of his sermons delivered an acerbic attack on Mnangagwa’s government as a ‘blood thirsty’ government. The study explored the messages of Mawarire and Mpandasekwa using the socio-theological lenses as guided by Rawls’ theory of civil disobedience.Contribution: This study locates #ThisFlag activism in the context of toxic transformative politics in Zimbabwe. In addition, it contributes to our understanding of the relationship between religion and politics in an unstable political and economic setting. It calls for a re-thinking of the role of the church in Zimbabwean society and discusses the state’s response to those deemed to be not towing the line. It shows that while some religious organisations and groups are too keen to be co-opted by the regime, some have effectively resisted this and have become combative as they fight for people’s rights. Another important contribution is located in how these pastor-cum-activists have harnessed social media to amplify their voices and to reach huge audiences beyond the pulpit. The study is important because it contextualises the role of religion in the country’s contemporary politics, and this fits into the scope of the journal in that it is a multidisciplinary study of both religion and politics.